(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2021)
In the manuscript [1] we derived the general Doppler effect equations. In order to prove the correctness of the equations, it remains to define an adequate coordinate system. We have argued that such a coordinate system cannot be chosen arbitrarily but is determined by the direction between the receiver at the time when the signal is received and the sender at the time when the signal is emitted. In this manuscript, several experiments have been proposed to prove the existence of such a coordinate system. In addition, we will determine the velocities at which the sender and receiver of the signal move and the distance between them.